POE-Based E-Module (Predict, Observe, and Explain): Improving Students' Critical Thinking Skills on Kinetic Theory of Gases - Maryam Aulia; Hadma Yuliani (CV FOUNDAE, 2022)
Based on interviews and observations, students' critical thinking skills at SMAN 5 Palangka Raya could have been more optimal. Therefore, the researchers offer a solution by using POE-based e-modules. This study aimed to see the improvement in critical thinking skills after using the POE-based e-modules in physics learning. This research method is quantitative with a one-group pretest-posttest design. Students critical thinking skills were determined usinga description test and analyzed using the N-Gain calculation. Based on the purposive sampling technique, the sample of this study was class XI MIPA 2 with 25 students. The result of this study was an increase in critical thinking skills after implementing a POE-based e-module, as indicated by an N-Gain of 0.73 (high category). This study concludes that POE-based e-modules can improve students' critical thinking skills.